Osteoporotic bone microstructure by collagenase etching. Issue 6 (June 1989) - Mackie, I G; Green, M; Clarke, H; Isaac, D H
Abstract : Collagenase etching has been used to show the microstructure of bone from patients suffering from primary osteoporosis. Both polished and unpolished surfaces of trabecular bone from femoral heads were treated with collagenase solution before study in the scanning electron microscope. The polished surfaces show the mineral component of this bone as small rounded units approximately 10-20 nm across, which aggregate to form a continuous phase of contiguous spheroidal particles approximately 100 nm across. Lamellations are clearly seen to be due to the removal of collagen fibres up to approximately 200 nm across, fibres in adjacent lamellae being arranged approximately perpendicular to each other. The unpolished surfaces also show small rounded units, which aggregate into rods of mineral approximately 100 nm across. Although these rods form a connected system, they are loosely packed, compatible with their being interspersed with the collagen fibres in vivo. This model for the detailed microstructure of bone is consistent with specimens from a number of other sources and shows no features unique to osteoporosis.